Toward Hydrogen Sulfide Based Therapeutics: Critical Drug Delivery and Developability Issues. Issue 1 (27th February 2017) - Zheng, Yueqin; Yu, Bingchen; De La Cruz, Ladie Kimberly; Roy Choudhury, Manjusha; Anifowose, Abiodun; Wang, Binghe
Abstract: Hydrogen sulfide (H2 S), together with nitric oxide (NO) and carbon monoxide (CO), belongs to the gasotransmitter family and plays important roles in mammals as a signaling molecule. Many studies have also shown the various therapeutic effects of H2 S, which include protection against myocardial ischemia injury, cytoprotection against oxidative stress, mediation of neurotransmission, inhibition of insulin signaling, regulation of inflammation, inhibition of the hypoxia‐inducible pathway, and dilation of blood vessels. One major challenge in the development of H2 S‐based therapeutics is its delivery. In this manuscript, we assess the various drug delivery strategies in the context of being used research tools and eventual developability as therapeutic agents.